The Improving Student’s Vocabulary through Rewriting Song Lyric in “The Shawn Mendes Foundation Playlist” - Bayu Laveresa; AB Prabowo; Ririn Ambarini (Aphorisme: Journal of Arabic Language, Literature, and Education, 2023)
This study aimed to determine students' mastery of rewriting an English song for class X students of SMA Negeri 1 Comal and to discover students' difficulties in rewriting English song lyrics. This research was conducted at SMA Negeri 1 Comal. The sample for this research was class X students for the 2022/2023 school year; thirty-five students were taken as samples. In analyzing the data, the writer uses the percentage of scores in the student test, which aims to determine student mastery in doing the test. The writer found that the experimental class or the class was not given the treatment. One student experienced a decrease in grades compared to the pre-test scores, 28 students experienced an increase in grades, and six students had the same post-test scores as their pre-test scores. From the graph, the writer concludes that grammar has a small increase, meaning that only a few students can get high grammar scores, and the one that increases the most is ideal content, meaning that many students have no difficulty in making ideal content, while vocabulary and punctuation look more stable. This means that students are fine with working on these aspects. In conclusion, students experience difficulties in grammar aspects.